Hip or knee strengthening exercises. What is best to treat patellofemoral pain: A literature review (Research, Society and Development, 2023)
Patellofemoral pain syndrome (PFPS) is one of the diseases that affect the ends of the knee. To improve functionality and decrease pain, affected patients often undergo a guided rehabilitation program. Traditional programs have focused on quadriceps strengthening and other knee-focused exercises, but current literature proposes that adding hip muscle strengthening may improve results. Hip muscle strengthening and quadriceps strengthening are common training exercises for patellofemoral pain syndrome (SDFP). SDPF generated by insufficient strength of the hip abductor and external rotator muscles has been of interest, but these exercise movements may increase the lateral vector force of the patella and deserve clarification. Thus, the objective of this article was to review randomized clinical trial studies and compare strengthening exercises for the hip and knee extensor muscles and analyze which brings the most results in the treatment of SDPF. Hip and knee strengthening is effective and superior to knee strengthening alone for decreasing pain and improving activity in people with patellofemoral pain. Both rehabilitation approaches led to improvements in self-reported function, objective function, and hip strength. This literature review further supports the importance of proximal musculature as a key element in the rehabilitation of people with PFPS.